(untitled) (KYAMC Journal, 2017)
In less developed country like Bangladesh, perinatal asphyxia remains a major cause of death and disability. Disorders of electrolytes are one of the common derangements encountered in critically ill asphyxiated neonates. It may remain unrecognized leading to morbidity and mortality irrespective of the primary problem. Syndrome of inappropriate secretion of ADH (SIADH) causes hyponatraemia in perinatal asphyxia. Metabolic acidosis may further exaggerate hyponatraemia. Where as in hypernatraemia there is an absolute or relative deficit of water in relation to body sodium. Hyponatraemia and hypernatraemia may aggravate the neurological morbidity in asphyxiated infants. Metabolic acidosis may causes hyperkalamia. On the other hand respiratory acidosis may cause hypochloraemia and renal tubular damage in perinatal asphyxia may further cause loss of potassium leading to hypokalaemia. This study has been conducted to find out the pattern of electrolyte abnormalities in asphyxiated neonates. In the study out of 133 asphyxiated babies 40 (30.1%) were hyponatremic. Hypokalaemia observed in 8 (6.0%) asphyxiated babies. Hyperkalaemia was found in 28 (21.1%) asphyxiated neonates in this study. Immediate measurements of serum electrolyte followed by appropriate fluid and electrolytes therapy can reduce the overall morbidity and mortality in asphyxiated neonates. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 775-779